Interdisziplinäre Teams in inklusiven Schulen: Eine ethnografische Studie zu Fallbesprechungen in multiprofessionellen Gruppen - Labhart, David (transcript, 2019)
Interdisciplinary cooperation is generally regarded as desirable. But how does a multi-professional group work together at all?